Education and science: current trends - Serebrennikova A. V., Goppe G. G., Kirgin D. S., Pokhomchikova E. O., Pogodaeva A. N., Baranov G. V., Khviiuzov M. A., Galashev A. N., Musina R. I., Danilchenko S. L., Rukina S. N., Amerzhanova Z. M., Isymov D. K., Kireeva E. V. (Education and science: current trends, 2017)
in a complicated economic situation in Russia, the value of the effectiveness of the state financial policy increases. This monograph discusses the key problems of organization public finance of Russia and ways to solving problems. Negative trends in the dynamics of macroeconomic indicators require an adjustment to the implementation of financial policy to be done. Author suggest target areas of the country's financial policies: stabilization. In the corresponding financial situation the key direction in order to formation of adequate government financial policy is a balance between the objectives of the finance stabilization and stimulate economic growth to be found.
Keywords: инновационное развитие; эффективность; финансовая система; государственные финансы; effectiveness; модернизация экономики; бюджетный дефицит; financial system; budget deficit; public finance; modernization of the economy; innovative development of the economy; использование бюджетных средств; the using budgetary funds